Kinetics And Optimization Studies Of Pressed Pericarp Fibers Pretreated With Organosolvent - Hii, Kiew Ling (2012)
The existence of lignin in pressed pericarp fibres (PPF) could inhibit the cellulolytic microorganisms from reacting with cellulose which directly inhibits the cellulolytic enzyme activities. In order to increase the susceptibility of cellulose, PPF was treated with organic solvent under high pressure and temperature in a high pressurized reactor (HPR). Monohydric alcohols (propanol) showed better delignification and hydrolysis at 38.5% and 46.1%, respectively. Ethanol was chosen as pretreatment solvent for further screening of catalyst due to its wide availability and economical perspective.